In vivo resorption of injectable apatitic calcium phosphate cements: Critical role of the intergranular microstructure. Issue 2 (29th April 2019) - Le Ferrec, Myriam; Mellier, Charlotte; Lefèvre, Francois‐Xavier; Boukhechba, Florian; Janvier, Pascal; Montavon, Gilles; Bouler, Jean‐Michel; Gauthier, Olivier; Bujoli, Bruno
Abstract: The in vivo resorption rate of two injectable apatitic calcium phosphate cements used in clinics (Graftys® HBS and NORIAN®) was compared, using a good laboratory practice (GLP) study based on an animal model of critical‐sized bone defect. To rationalize the markedly different biological properties observed for both cements, key physical features were investigated, including permeability and water‐accessible porosity, total porosity measured by mercury intrusion and gravimetry, and microstructure. Due to a different concept for creating porosity between the two cements investigated in this study, a markedly different microstructural arrangement of apatite crystals was observed in the intergranular space, which was found to significantly influence both the mechanical strength and in vivo degradation of the two calcium phosphate cements.